Key determinants of consumers’ decision on the purchase of wristwatches in the Serbian market - Nuševa, Daniela; Marić, Radenko; Vukmirović, Goran; Macura, Nikola (Anali Ekonomskog fakulteta u Subotici, 2024)
The covid-19 pandemic and other global challenges that have appeared in the past years have caused market transformation and crucial changes on the demand side, forcing manufacturers and retailers to rethink their sales and marketing strategies. In particular, high-frequency durable consumer products such as wristwatches have proven to be sensitive. In this regard, this work aims to analyze the needs of consumers and define the indicators that directly influence the decision to buy wristwatches in the market of the Republic of Serbia. The research was organized in two phases. Theoretical research has identified indicators influencing purchase decisions, such as price, brand, design, ease of use, and warranty. Empirical research examined their influence on the purchase decision depending on different segments of respondents: gender, age, education, and employment status. The obtained results showed significant differences as to how the mentioned indicators influence the purchase decision, depending on the demographic indicators. Based on the presented results, a set of measures was proposed to improve the sales and marketing strategy for placing wristwatches on the market of the Republic of Serbia. Guidelines for future research are outlined in the paper.